2010
DOI: 10.1179/136485910x12607012373759
|View full text |Cite
|
Sign up to set email alerts
|

Application of real-time PCR for the differentiation ofEntamoeba histolyticaandE. disparin cyst-positive faecal samples from 130 immigrants living in Spain

Abstract: In an effort to improve the diagnosis of intestinal amoebiasis, a real-time PCR has been used for the detection and differentiation of Entamoeba histolytica and E. dispar infections in African or South American immigrants who live in Spain. Faecal samples from all of the 130 subjects had apparently been found to contain E. histolytica/E. dispar cysts by microscopical examination. Using the real-time PCR, E. histolytica DNA was detected in faecal samples from only 10 (7.7%) of the immigrants, with E. dispar DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 15 publications
2
24
1
Order By: Relevance
“…The ability to differentiate between pathogenic E. histolytica and non-pathogenic Entamoeba species is clinically significant. Results concur with a prevalence study of Entamoeba in immigrants in Spain that showed that the majority of cyst-positive samples detected by microscopy were E. dispar and do not require treatment 5 .…”
Section: Discussionsupporting
confidence: 77%
“…The ability to differentiate between pathogenic E. histolytica and non-pathogenic Entamoeba species is clinically significant. Results concur with a prevalence study of Entamoeba in immigrants in Spain that showed that the majority of cyst-positive samples detected by microscopy were E. dispar and do not require treatment 5 .…”
Section: Discussionsupporting
confidence: 77%
“…Hence, we indicated that of 23 positive samples in multiplex PCR test, 13 and 10 samples were positive for E. dispar and E. histolytica, respectively. Unlike our results, previous studies indicated that E. dispar was approximately ten times more common in stool samples than E. histolytica [19,21].…”
Section: Discussioncontrasting
confidence: 56%
“…Both conventional and real-time PCRs have proven to be more sensitive and specific than microscopic examination for the detection of E. histolytica and E. dispar in single stool samples (455,460). In developed settings, PCR is more useful for detection of E. histolytica in stools than antigen detection tests due to the higher sensitivities observed for PCR and the reduced chance of cross-reactivity with other Entamoeba species (167,397,460). However, PCR has yet to become the mainstream for the detection of parasites in the clinical laboratory, even in developed countries, due to the need for specialized equipment, dedicated molecular areas, specified workflow, and associated costs.…”
Section: Entamoeba Speciesmentioning
confidence: 99%